The influence of electronic word of mouth (eWOM) via Instagram on repurchase intention: The Influence of Electronic Word of Mouth (EWOM) on the Instagram Application on Repurchase Intention of Skintific products - Juita, Salsabila; Abror, Abror (Marketing Management Studies, 2025)
This study aims to examine the effect of electronic word of mouth (ewom) on the Instagram application on the intention to repurchase skintific products. This research is a quantitative study with a sample method, namely purposive sampling. The sample in this study were 130 respondents. Data analysis was carried out using the Structural Equation Modeling SEM method using Smar PLS 4.0 software. This study uses the information adoption model of ewom. These results show that information quality has a significant positive effect on information usability. Information quantity has a significant positive effect on information usability. Information credibility has an insignificant positive effect on information usefulness. Information usefulness has a significant positive effect on information adoption. Information adoption has a significant positive effect on repurchase intention.